Acute respiratory failure and CNS-depressing drugs. Issue 667 (May 1981) - Gray, J. M.; Henry, D. A.; Paice, B.; Gettinby, G.; Moran, F.; Lawson, D. H.
Abstract : Data from a drug surveillance programme were analysed to estimate the frequency with which patients with a diagnosis of respiratory failure had been exposed to CNS-depressing drugs. Eleven out of 37 patients with respiratory failure had received such medication. A detailed comparison of these patients and controls admitted to hospital because of respiratory disease who did not develop respiratory failure failed to reveal significant differences in drug usage. This unexpected finding suggests that patients with respiratory disease of equal severity may vary greatly in their tendency to develop carbon dioxide retention following administration of drugs with respiratory depressant properties.